Analysis of the therapeutic effect of right mid-axillary approach in the surgical treatment of ASD and VSD in children - Fuqiang Li; Tian Cheng; Mingliang Yan; Tao Li; Tianchen Zhang; Yaoxuan Huang; Jian Tang (Journal of Cardiothoracic Surgery, 2024)
Abstract Background To compare the therapeutic effects of right vertical infra-axillary thoracotomy (RVIAT) and Standard Median Sternotomy (SMS) in the repair of atrial septal defect (ASD) and ventricular septal defect (VSD), and to evaluate the safety and effectiveness of right subaxillary incision technique in the surgical treatment of common congenital heart disease (CHD) in children. Methods Data of children diagnosed with ASD repair or VSD repair at our center from September 2019 to September 2022 were collected. Based on propensity score matching, 214 children (107 in the RVIAT group and 107 in the SMS group) who completed ASD repair surgery and 242 children (121 in the RVIAT group and 121 in the SMS group) who completed VSD repair surgery were selected for the study. The perioperative and follow-up data of the two surgical approaches were compared to evaluate clinical efficacy. Results There was no statistically significant difference (p > 0.05) between the two surgical approaches in terms of surgical time, aortic occlusion time, total amount of ultrafiltration fluid, ICU stay time, and hospital stay; The intraoperative blood loss and total postoperative drainage fluid in the RVIAT group were lower than those in the SMS group (p < 0.05); The incidence of postoperative thoracic deformities in the SMS group is higher than that in the RVIAT group. Conclusion The safety and effectiveness of the two approaches are similar, but RVIAT has less intraoperative bleeding, less postoperative drainage fluid and tube time, and better concealment and cosmetic effects, which is worthy of further clinical promotion and application.